FINANCIAL INDICATORS OF SOCIO-ECONOMIC INTERACTION OF STEAKHOLDERS - Тимощук, Мирослава; Шишковський, Сергій; Яворська, Наталія (Socio-economic relations in the digital society, 2019)
Experience of economically developed countries shows that socio-economic interaction (SEV) of stakeholders is a determining factor in the long-term development of enterprises, in the process of which the interests of interested parties are coordinated, conditions are created for preservation and restoration of the environment, socio-economic development of enterprises, meeting the needs of consumers and increasing the population life level. Socio-economic is interaction in the field of socio-economic relations, observing the principles of social responsibility for the environment and the adoption of moral virtues and ethical norms of social partnership in the internal and external environment. The parties to the socio-economic interaction are the environment (ecosystem), the internal environment (enterprise) and the external environment. In the process of interaction, each side seeks to achieve its goal: the environment — to preserve the ecosystem;  internal environment — to provide economic development of the company with observance of the provisions as for socially responsible activities; the external environment — to balance economic and social interests. Since the primary social responsibility of the company is to ensure business activity and efficiency of its functioning, the article focuses on the formation of basic indicators of SEV enterprises with an internal environment, which consists of employees of the enterprise, fixed assets, technology, management system, etc. Forming a subsystem of SEV financial indicators in enterprises with an internal environment, it is necessary to rely on the principles of convincing, binding and consistent. In this case it is expedient to distinguish the following subgroups of indicators: economic efficiency; labor; staff development. The basic financial indicators of SEVs in enterprises with an internal environment include the following, which correspond to the content of distinct subgroups, namely: indicators of profitability of products; business activity; working and rest conditions; wage conditions; development of corporate culture and professional skills of employees of the enterprise. The scientific novelty of the article is to consider the activities of enterprises as the process of their socioeconomic interaction with interested parties, in which each party seeks to achieve the goal set before it. The developed set of indicators of SEV assessment at enterprises by substantiating the choice of unit (basic) indicators of the state and dynamics of interaction between enterprises with the internal environment will allow to reconcile the socio-economic interests of enterprises with the conditions and needs of the functioning environment. Conscious introduction of the concept of management of SEVs at enterprises will lead to the emergence of interrelated image and social results that directly or indirectly affect the financial and economic outcomes of enterprises. Further research is associated with the formation of a system of indicators for assessing the state and dynamics of SEVs, which are based on non-fi nancial reporting of enterprises, as well as the development of methods for positioning enterprises in the space of socio-economic interaction.
Keywords: stakeholder interaction; financial indicators; aggregate; evaluation; results